2011
DOI: 10.1590/s1807-59322011001000013
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of MGMT promoter methylation status with gene and protein expression levels in glioblastoma

Abstract: OBJECTIVES:1) To correlate the methylation status of the O6-methylguanine-DNA-methyltransferase (MGMT) promoter to its gene and protein expression levels in glioblastoma and 2) to determine the most reliable method for using MGMT to predict the response to adjuvant therapy in patients with glioblastoma.BACKGROUND:The MGMT gene is epigenetically silenced by promoter hypermethylation in gliomas, and this modification has emerged as a relevant predictor of therapeutic response.METHODS:Fifty-one cases of glioblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 37 publications
4
56
0
2
Order By: Relevance
“…Assessment of MGMT expression by immunochemistry, a cost-effective method, has also been proposed, but it did not seem to correlate well with promoter methylation (Uno et al 2011). Since then, various methylation-independent mechanisms of MGMT expression have been described, explaining this discrepancy (Lavon et al 2007, Kitange et al 2012, Kohsaka et al 2012, Kreth et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of MGMT expression by immunochemistry, a cost-effective method, has also been proposed, but it did not seem to correlate well with promoter methylation (Uno et al 2011). Since then, various methylation-independent mechanisms of MGMT expression have been described, explaining this discrepancy (Lavon et al 2007, Kitange et al 2012, Kohsaka et al 2012, Kreth et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The above changes could cause incomplete downregulation of MGMT protein expression. In addition to methylation of CpG islands in the promoter region, which is the most significant mechanism of MGMT regulation that suppresses MGMT transcription [26,27], other mechanisms, such as MGMT genetic changes [28,29], histone modifications [30,31], p53 derangement [32,33] and post-transcriptional regulation [34,35] could also lead to MGMT silencing. Absence of MGMT protein expression (IHC-) in 15.8 % of our unmethylated (MSP-) GBM cases (Table 3) would be the result of other MGMT silencing mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the effects of MGMT on glioma, Uno et al (2011) found that the positive rate of MGMT methylation was 43.1%, and that methylation was related to low gene expression. Esteller et al (2000) indicated that 40% of patients experienced MGMT promoter methylation, and higher levels of methylation were associated with a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…These results support the conclusion that MGMT methylation plays an important role in the occurrence and development of glioma. MGMT promoter methylation results in gene silencing (Hegi et al, 2005;Uno et al, 2011), and is therefore considered a predictive factor for evaluating the effect of treatment by TMZ in glioblastoma multiforme (GBM) patients (Hegi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%